Typologie de l’implantation de la flore spontanée en ville dense, - Xavier Lagurgue; Flavie Mayrand; Philippe Clergeau (VertigO)
The adaptation of cities to global warming requires the search for economic solutions to be mobilized on a large scale. In this context, the greening of the built envelopes is now known to contribute to the reduction of islands of heat and the benefits of nature in the city. Among the existing vegetation devices, the colonization of the supports built by the spontaneous plants is free and holds the attention. However, spontaneous vegetation is often associated in professionals with the potential degradation of buildings and experiments are rare. On the other hand, the research concerning the colonization of buildings is not addressed to the architectural ecodesign for rupicolous and ruderal species. The aim of this article is to characterize built-up situations identified by their capacity to accommodate the development of spontaneous plants. The method used was to establish vegetation drawings in their built environment. The scaling of plants compared to constructed structures shows the dynamics of interactions. The implantation points were then described and analyzed to extract interaction characteristics between the plant and the built biotope. The data obtained relate to architectural criteria for plant establishment, criteria for characterizing the plant implantation point on a built support and an attempt to evaluate the impact of these criteria on certain plant functions. This study proposes a first approach aimed at the architectural ecodesign of envelopes in order to favor the colonization of buildings by vegetation.